Design methodology for using blockchain in swarm robotics - Sathishkumar Ranganathan; Muralindran Mariappan; Karthigayan Muthukaruppan (Institute of Electrical and Electronics Engineers, 2021)
Swarm robotics is an evolving realm that aims to achieve a common goal in coordinated way. But the current communication and control mechanism between the robots is not secure, efficient, capable, and it is more centralized. Blockchain, a decentralized, transparent, and immutable P2P communication technology, is the right fit to pair with swarm robotics. This paper discusses the current challenges in paring blockchain with swarm robotics and the applied methodology for the amalgamation of these futuristic technologies.